New directions in interpreting the millon clinical multiaxial inventory-III (MCMI-III) - Craig, Robert J. (John Wiley & Sons, 2005)
New Directions in Interpreting the Millon Clinical Multiaxial Inventory, edited by a leading MCMI researcher and featuring contributions from internationally renowned scholars in personality assessment, presents new methods of interpretation and new clinical applications for this classic objective measure of personality. This dynamic new handbook discusses issues related to the effect of culture on MCMI-III results and controversies regarding its forensic applications, and presents research related to the MCMI-III's diagnostic power with regard to diagnosis and malingering.